The Influence of Differentiation Strategy to Superiority Competing in the Creative Industry - Muhammad Agung Dharmajaya (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
This study aims to analyze the effect of differentiation strategy on superior competitiveness in the creative industry. The creative industry faces increasingly fierce competition, so business actors strive to create unique products, innovations, and trademarks that are able to differentiate themselves from competitors. Differentiation strategy is seen as one of the strategic approaches that can increase competitiveness and business sustainability. This study uses a quantitative study method with a survey approach. Data were collected by distributing questionnaires to creative industry business actors in Sumedang Regency as research respondents. A total of 93 samples were obtained. Data analysis used included validity tests, reliability tests, and simple regression analysis to examine the effect of differentiation strategy on superior competitiveness. The results of the study indicate that differentiation strategy has a positive and significant effect on superior competitiveness in the creative industry. This finding indicates that the better the implementation of differentiation strategies, such as product innovation, quality, design, and service, the higher the superior competitiveness of creative industry actors. This study is expected to provide practical contributions to industry players in formulating effective business strategies and serve as a reference for further research.